Supernatant of Lactobacillus spp. isolated from vaginal secretion and its antagonistic activity against Candida species - Chinchay, Gerald (2024)
Vaginal candidiasis is a common and recurrent infection in women, and the use of probiotics, such as Lactobacillus spp., has been proposed as a therapeutic alternative due to their ability to inhibit the growth of pathogens. The aim of the study was to evaluate the inhibitory activity of Lactobacillus spp. strains isolated from vaginal secretions against C. albicans, C. glabrata, and C. krusei. Samples were obtained from healthy women, and the Lactobacillus spp. strains were identified through phenotypic and biochemical tests. Sensitivity disks impregnated with the supernatant of the Lactobacillus spp. strains were prepared, and their antagonistic effect against Candida spp. species was evaluated by performing three repetitions per species using the disk diffusion method on Mueller-Hinton agar. It was observed that the L3 strain of Lactobacillus spp. had an inhibition zone of up to 10 mm against C. albicans and C. glabrata. The Lactobacillus spp. strains isolated from vaginal secretions show potential to inhibit the growth of C. albicans and C. glabrata.